A SHORT STUDY ON THE CURRENT STATUS OF WEB APPLICATIONS SECURITY IN AFRICA AND ACROSS THE WORLD - Chady, Dougesha (MATTER: International Journal of Science and Technology, 2019)
This new digitalized era is bringing lots of advantages in the world of business today as many processes are being automated through web applications to ease the fast paced work life of people making things more rapidly and efficiently. However, due to some weaknesses in the configuration and development of web applications, it becomes easy for hackers to identify and exploit loopholes found in web applications. For that reason, it becomes vital to emphasize on the importance of web security. Therefore, a qualitative research methodology is used to investigate on the topic. To elaborate, the aim of this paper is to identify the common causes of data theft that occurred during the last few years, especially regarding the outbreak that happened in South Africa. Finally, few researches and development done in the area of security like SQl injection, Cross site scripting and others were examined.